The effectiveness of experiential learning on students' understanding of science and technology - Rika Yuliana; Wasino Wasino; Nuni Widiarti (Inovasi Kurikulum, 2025)
Learning through the experiential learning model encourages students to experiment dynamically and comprehensively. This research aims to see the effectiveness of the experiential learning learning model. This research uses a quantitative experimental research design as its methodology. The population of this study was fifth-grade students at Gugus Waru Elementary School, Parung District. Random sampling is the sampling strategy used in this research. Data collection techniques include tests, observation, and documentation. SPSS was used for data analysis. Validity, reliability, difficulty level of questions, and differentiation tests are tools used in research analysis. Furthermore, normality, homogeneity, hypothesis testing, N-Gain, and T-tests are prerequisite tests. The research results were concluded from the validation results of 88 material experts and received a very suitable category based on the evidence provided. Media expert validation scored 90 in the very appropriate category, while language validation obtained 64 in the appropriate category. The practical category is represented by the average of all validation findings, which is 80.6%. This makes this guidebook, which experts verified regarding content, language, and media, suitable for use.   Abstrak Pembelajaran melalui model experiential learning mendorong peserta didik untuk bereksperimen secara dinamis dan komprehensif. Tujuan penelitian ini adalah untuk melihat efektivitas model pembelajaran experiential learning. Penelitian ini menggunakan desain penelitian eksperimen kuantitatif sebagai metodologinya. Populasi penelitian ini adalah peserta didik kelas V SD Gugus Waru Kecamatan Parung. Random sampling merupakan strategi pengambilan sampel yang digunakan dalam penelitian ini. Teknik pengumpulan data menggunakan tes, observasi dan dokumentasi. SPSS digunakan untuk analisis data. Validitas, reliabilitas, tingkat kesukaran soal dan tes pembedaan soal merupakan alat yang digunakan dalam analisis penelitian. Selanjutnya uji normalitas, homogenitas, uji hipotesis, N-Gain, dan uji T merupakan uji prasyarat. Adapun hasil penelitian disimpulkan dari hasil validasi ahli materi sebanyak 88 orang dan mendapat kategori sangat sesuai berdasarkan bukti-bukti yang diberikan. Validasi ahli media memperoleh skor 90 dengan kategori sangat sesuai, sedangkan validasi bahasa memperoleh skor 64 dengan kategori sesuai. Kategori praktis diwakili oleh rata-rata seluruh temuan validasi yaitu sebesar 80,6%. Hal ini menjadikan buku pedoman yang telah diverifikasi oleh para ahli dari segi isi, bahasa dan media ini layak untuk digunakan. Kata Kunci: media audio visual; model experiential learning; pemahaman konsep IPAS